Synthesis, Structure and Properties of Novel S-Substituted BIS-1,2,4-Triazoles - Karpun, Ye.; Карпун, Євген Олександрович (My University, 2021)
The aim of the work was to describe the method of combining two 1,2,4-triazole systems in a molecule, the alkylation reaction of the thiol group to obtain the previously undiscovered S-derivatives of 1,2,4-triazole and the fragmentation pathway of the substances under hard ionization using gas chromatography-mass spectrometry. The structures of the synthesized compounds were confirmed by elemental analysis, 1H and 13C NMR spectroscopy and GC-MS analysis. The characteristic signals for S-alkyl residues were observed in the region typical for aliphatic compounds. The fragmentation of molecules was represented by the gradual cleavage of radicals and the opening of the second 1,2,4-triazole heterocycle.
Keywords: 1,2,4-triazole; heterocyclic compound; synthesis; fragmentation pathway